2012
DOI: 10.3402/qhw.v7i0.18463
|View full text |Cite
|
Sign up to set email alerts
|

An escape from agony: A qualitative psychological autopsy study of women's suicide in a post-conflict Northern Uganda

Abstract: We set out to investigate suicide among women in a post-conflict context in Northern Uganda using qualitative psychological autopsy interviews. Three to five relatives and friends for each of the three suicides recruited were interviewed (N=11). Through interpretative phenomenological analysis (IPA) we found that the women all had been through traumatic experiences attributable to the protracted war/conflict between the rebel groups and Ugandan Government armed forces. Nevertheless, the decision of self-inflic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…In some respondents, PSTD symptoms could have persisted sevenyears after the conflict possibly because there were no well coordinated and effective medical, psychological and social welfare programs in the study communities [ 7 , 12 , 28 ]. War is likely to affect the functional capacity of government and other service agencies to deliver public mental health services [ 7 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In some respondents, PSTD symptoms could have persisted sevenyears after the conflict possibly because there were no well coordinated and effective medical, psychological and social welfare programs in the study communities [ 7 , 12 , 28 ]. War is likely to affect the functional capacity of government and other service agencies to deliver public mental health services [ 7 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the socio-demographic factors significantly associated with MDD in this study were indices of socio-economic disadvantage in this post-conflict situation in northern Uganda, these were: female gender, increasing age, being widowed, separated and divorced, and having no formal education, with female gender retaining statistical significance in the final multivariate analysis. Previous studies in conflict and post-conflict settings have reported the following socio-demographic factors to be associated with MDD: female gender [ 2 - 4 , 8 , 12 , 14 ]; increasing age [ 42 ]; being widowed, separated and divorced [ 2 , 8 , 43 ] and having no formal education [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several factors have been reported to be associated with MDD in conflict settings and these include: female gender [ 2 - 4 , 8 , 12 - 14 ]; indices of socio-economic disadvantage-widowhood, disability, being married for women, unemployment, no formal education, abject poverty, broken families, long periods of displacement, experiencing ill health without medical care [ 2 , 3 , 8 , 13 ]; and degree of exposure to traumatic events [ 2 - 5 , 8 , 13 , 15 ]. Apart from exposure to traumatic events reported by Wong and Colleagues [ 10 ], it is not known which other factors continue to contribute to the risk of MDD in the post-conflict situation after war has ceased and communities are re-settled.…”
Section: Introductionmentioning
confidence: 99%
“…In many African countries, developing indices of suicidal behaviour is difficult due to the absence of national death registers, poor records at service departments (including police and medical facilities), civil conflict, culture and stigma among others (Kinyanda, 2011;Mugisha, 2012;De Leo et al, 2013). One of the established risk factors of suicidal behaviour is comorbid mental illness (Ovuga, Boardman &Wassserman;2005;Bellin & Bruschi, 1996;Kinyanda et al 2012). Data on the comorbidity of mental illness and suicidal behaviour in sub-Saharan African settings, especially those affected by political conflict is sparse.…”
mentioning
confidence: 99%